Fishermen's Fishing Activities and Socio-Economic Conditions (Case Study of Fishermen in Warbal Village, West Kei Kecil District, Southeast Maluku Regency) - Masbaitubun, Novena; Salakory, Melianus; Salampessy, Djalaludin (Program Studi Pendidikan Geografi FKIP Universitas Pattimura, 2023)
The fishing activities of fishermen play a significant role in meeting the community's economic needs and pose an important challenge in increasing their income. This research examines the fishing activities of fishermen and the socio-economic conditions in Warbal Village, Kei Kecil Barat District, Maluku Tenggara Regency, Indonesia. The research uses a descriptive-analytic approach and involves primary data obtained through interviews, observations, questionnaires, and documentation. The research findings indicate that most fishermen in Warbal Village rely on fishing as their primary livelihood. They use traditional fishing tools such as nets and arrows in their fishing activities. The duration of fishing varies, with some fishermen engaging in nighttime fishing to increase their catch. Fishing activities generally commence in the morning. The socio-economic conditions of fishermen in Warbal Village are challenging, with low incomes often insufficient to meet daily needs. Their expenses tend to exceed their income, leading to difficulties for some fishermen in sustaining continuous fishing activities.